Advances in remote sensing of the daytime ionosphere with EUV airglow. Issue 9 (28th September 2016) - Stephan, Andrew W.
Abstract: This paper summarizes recent progress in developing a method for characterizing the daytime ionosphere from limb profile measurements of the OII 83.4 nm emission. This extreme ultraviolet emission is created by solar photoionization of atomic oxygen in the lower thermosphere and is resonantly scattered by O + in the ionosphere. The brightness and shape of the measured altitude profile thus depend on both the photoionization source in the lower thermosphere and the ionospheric densities that determine the resonant scattering contribution. This technique has greatly matured over the past decade due to measurements by the series of Naval Research Laboratory Special Sensor Ultraviolet Limb Imager (SSULI) instruments flown on Defense Meteorological Satellite Program (DMSP) missions and the Remote Atmospheric and Ionospheric Detection System (RAIDS) on the International Space Station. The volume of data from these missions has enabled a better approach to handling specific biases and uncertainties in both the measurement and retrieval process that affect the accuracy of the result. This paper identifies the key measurement and data quality factors that will enable the continued evolution of this technique into an advanced method for characterization of the daytime ionosphere. Key Points: The OII 83.4 nm airglow emission can be used to characterize the daytime ionosphere Biases can be addressed with complementary spectral features and measurement of neutral densities Ambiguity in results can be addressed with better instrument responsivity and characterization